2011
DOI: 10.1093/cercor/bhr238
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Motor System in Binding Abstract Emotional Meaning

Abstract: Sensorimotor areas activate to action- and object-related words, but their role in abstract meaning processing is still debated. Abstract emotion words denoting body internal states are a critical test case because they lack referential links to objects. If actions expressing emotion are crucial for learning correspondences between word forms and emotions, emotion word–evoked activity should emerge in motor brain systems controlling the face and arms, which typically express emotions. To test this hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
154
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 103 publications
(156 reference statements)
10
154
1
Order By: Relevance
“…Increased activation in the somatosensorylingual cortex during emotional decision-making is connected in healthy controls with an individual's awareness of his or her emotional state and with the control that the language system has over perceiving of one's emotions. 59,60 Thus, we can conclude that relative to the MDD-FHP group, the HC-FHP group has more potential for paying attention to external emotional cues and to their own emotional reactions to these cues.…”
Section: Figmentioning
confidence: 86%
See 1 more Smart Citation
“…Increased activation in the somatosensorylingual cortex during emotional decision-making is connected in healthy controls with an individual's awareness of his or her emotional state and with the control that the language system has over perceiving of one's emotions. 59,60 Thus, we can conclude that relative to the MDD-FHP group, the HC-FHP group has more potential for paying attention to external emotional cues and to their own emotional reactions to these cues.…”
Section: Figmentioning
confidence: 86%
“…An increase characteristic of the HC-FHP group was also observed during both emotion processing and attention shifting in an area commonly associated with executive control, the left IPG, [53][54][55][56][57] and in a region involved in language operations, the left SuMG. [58][59][60] Both regions participate in managing emotional arousal either through focusing attention on and off the affective cues or through naming emotional states and organizing them. [61][62][63] It can be concluded that vulnerability to MDD is characterized by increased sensory reactivity to emotional cues, both when attention is focused on them and when it is not.…”
Section: Figmentioning
confidence: 99%
“…Indeed, an fMRI study investigating the processing of emotion words (such as 'joy' and 'fear') showed activity not only in limbic emotion-processing areas (such as anterior cingulate and anterior insula), reflecting the affective meaning of these terms, but in motor areas overlapping with regions activated by overt action-related words (such as "write" and "lick"; Moseley, Carota, Hauk, Mohr, & Pulvermü ller, 2012).…”
mentioning
confidence: 99%
“…In turn reflecting how mirror neurons in the brain translate spatial positions of entities into sequences of motor programs, that enable us to visually locate, reach out and grasp an object [3]. Lately neuroimaging studies have demonstrated that the sensorimotor system provides a binding not only for word categories related to arm or face motion but also for verbs with an abstract emotional meaning [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive component analysis COCA, defined as an unsupervised learning of features resembling how we perceive the world, suggests that sensory structures can be modeled by reducing dimensionality and treating objects in space and time as linear mixtures [8]. Going beyond our initial COCA analysis of 30 action verbs [9], we here take 3 × 20 hand, face and emotion related action verbs used in the above neuroimaging study [4], and hypothesize that the force and spatial parameters which define action-based language might also be reflected in the co-variances of words underlying their latent semantic structure. And to explore to what degree these underlying structures might generalize we apply LSA based on two different large-scale text corpora HAWIK and TASA available online 12 .…”
Section: Introductionmentioning
confidence: 99%